Editorial - Ratnalikar, N. V. (Journal of Engineering Education Transformations, 2006)
With Engineering Education becoming an international service, there is a growing concern world over, about quality, standards and recognition. Consequent upon this trend, the debate on how Bench marks have to be evolved for ascertaining and assessing quality at different levels of higher education, is significant.